2022
DOI: 10.3989/revmetalm.212
|View full text |Cite
|
Sign up to set email alerts
|

Resistencia al desgaste y rendimiento durante procesos de extrusión a escala industrial de los aceros 100Cr6 y 21NiCrMo2 sometidos a tratamientos criogénicos

Abstract: Se ha investigado los efectos de diferentes parámetros de tratamiento térmico y criogénico como la temperatura y el tiempo de mantenimiento sobre la microestructura (cantidad de austenita retenida) y la dureza de moldes de extrusión producidos a partir de los aceros 21NiCrMo2 y 100Cr6. La matriz de extrusión del acero 21NiCrMo2 se cementó durante 22,5 h en una atmósfera de gas (25% CO, 35% N2, 40% H2) a 920 °C. Al final del proceso de cementación, la temperatura se mantuvo a 850 °C, que es la temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For steel subjected to CT at −196 °C for 24 h, this reduction was slightly higher (60%) [246]. In other work [228], Karaca et al reported that an application of −100 °C cryogenic treatment for 3.5 h improved wear performance by only 10%, but the treatment at −120 °C gave a 40% improvement in wear rate [234]. A CT duration of 24-36 h (at −185 or −196 °C) was recommended as optimal to achieve the best wear performance of bearing steels [24,151,244].…”
Section: Ball Bearing Steelsmentioning
confidence: 92%
See 3 more Smart Citations
“…For steel subjected to CT at −196 °C for 24 h, this reduction was slightly higher (60%) [246]. In other work [228], Karaca et al reported that an application of −100 °C cryogenic treatment for 3.5 h improved wear performance by only 10%, but the treatment at −120 °C gave a 40% improvement in wear rate [234]. A CT duration of 24-36 h (at −185 or −196 °C) was recommended as optimal to achieve the best wear performance of bearing steels [24,151,244].…”
Section: Ball Bearing Steelsmentioning
confidence: 92%
“…These results indicate that it is possible to increase the material toughness without sacrificing hardness through CT, owing to overall microstructural refinement (martensitic domains and η-carbide precipitates). Nevertheless, Karaca and Kumruoğlu [234] reported opposite results. The CVN impact toughness of AISI 52100 steel notably decreased with the application of CT at −120 °C for 2 h. This is rather surprising at first glance, but fractographic analyses revealed completely brittle fractures of cryogenically treated samples.…”
Section: Ball Bearing Steelsmentioning
confidence: 96%
See 2 more Smart Citations